Transformation Towards Sustainable Airports: A Review of Policies and Challenges in Indonesia - Suhanto Suhanto; Sukarwoto Sukarwoto; Moch Rifai; Irfan Irfan; Yuyun Suprapto; Hadi Prayitno (Utan Kayu Publishing, 2025)
The rapid growth of the aviation industry also presents significant challenges regarding environmental impact. In Indonesia, airports are facing pressure to reduce their carbon footprint and improve overall sustainability. This research aims to provide a clear picture of the policies and challenges of implementing sustainable airports in Indonesia. A systematic literature review was carried out using PRISMA guidelines, which aims to analyze knowledge regarding sustainability at airports. This research uses the Google Scholar database, Scopus from Elsevier, the Web of Science database from Clarivate, and the 2023 PT Angkasa Pura I and II sustainability reports. The results of the research show that sustainable airport policies focus on developing environmentally friendly airports by prioritizing environmental management and collaborating with various stakeholders. Environmentally sustainable airports have been implemented, but they are limited to large airports in Indonesia.